Comparison of the Effectiveness of Acceptance and Commitment Interventions, Positive Thinking, and Existential Therapy on Increasing Psychological Flexibility in Female Heads of Household - Nowzari, Mohammad; Navabinejad, Shokouh; Sharifirad, Gholamreza (KMAN Counseling & Psychology Nexus, 2026)
The present study was conducted with the aim of comparing the effectiveness of Acceptance and Commitment interventions, Positive Thinking, and Existential Therapy on increasing psychological flexibility in female heads of household. This research was a quasi-experimental study with a pretest–posttest design and a control group. The statistical population of the present study included female heads of household in District 2 of Qom. Since a sample size of 15 participants per group has been recommended for experimental studies, four groups of 15 participants each (a total of 60 participants) were selected through convenience sampling from among female heads of household. The participants were randomly assigned to four groups, including three experimental groups and one control group. The experimental groups received the intended interventions, whereas the control group received no intervention during the implementation of the study. The measurement instrument used in this study was the Hope Scale developed by Charles Richard Snyder and colleagues (1991). Data were analyzed using SPSS statistical software and multivariate analysis of covariance (MANCOVA). The results demonstrated that, regarding the variable of hope for life, there was a significant difference between Acceptance and Commitment Therapy and Positive Thinking Therapy (F = 41.42, p < .017), as well as between Positive Thinking Therapy and Existential Therapy (F = 57.21, p < .039). However, no significant difference was observed between Existential Therapy and Acceptance and Commitment Therapy (F = 82.09, p < .052). Therefore, it can be concluded that Acceptance and Commitment Therapy, Positive Thinking, and Existential Therapy can be utilized in the treatment programs of counseling centers to enhance psychological flexibility among female heads of household.